2007
DOI: 10.1042/bst0351593
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the design of new epoxy supports for enzyme immobilization–stabilization

Abstract: Multipoint covalent immobilization of enzymes (through very short spacer arms) on support surfaces promotes a very interesting 'rigidification' of protein molecules. In this case, the relative positions of each residue of the enzyme involved in the immobilization process have to be preserved unchanged during any conformational change induced on the immobilized enzyme by any distorting agent (heat, organic solvents etc.). In this way, multipoint covalent immobilization should induce a very strong stabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(155 citation statements)
references
References 69 publications
3
149
0
3
Order By: Relevance
“…Many studies have shown that the activity and stability of an immobilized enzyme can differ considerably from that of its soluble counterpart [28,29]. Therefore, the properties of the CLEAs were compared with those of the native SPase.…”
Section: Characterization Of Spase Cleasmentioning
confidence: 99%
“…Many studies have shown that the activity and stability of an immobilized enzyme can differ considerably from that of its soluble counterpart [28,29]. Therefore, the properties of the CLEAs were compared with those of the native SPase.…”
Section: Characterization Of Spase Cleasmentioning
confidence: 99%
“…(2) En soportes Eupergit C. En este caso la enzima se inmoviliza después de una adsorción de la enzima sobre el soporte (Mateo et al, 2007b). Esta enzima se inmovilizó previamente en este soporte en presencia del detergente triton X-100 para evitar adsorción interfacial de la enzima y alta fuerza iónica para forzar la adsorción de la enzima por otras regiones hidrofóbicas de la proteína (Barbosa et al, 2011).…”
Section: Metodología Experimentalunclassified
“…[38] Polymers with epoxide groups are widely used as solid supports for enzymes in catalytic processes and there is variety of commercially available products [e.g., Eupergit (Röhm Pharma/Evonik) or Sepabeads (Resindion SRL)]. [39] Turková and coworkers have shown that many kinds of proteins (trypsin, serum albumin, amyloglucosidase) can be coupled to a glycidyl methacrylate (GMA) copolymer. [40] The high reactivity of epoxides also offers a good possibility for modifications before immobilization of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…[40] The high reactivity of epoxides also offers a good possibility for modifications before immobilization of the protein. [39,41] The amount of bound BMP2 can be assessed by radiolabeling with 125 I, ELISA or BMP-receptor-binding assays (ELIRA). [12,16,42] Typically radiolabeling results in higher amounts of bound protein than is detected by immunoassays because also denaturated protein is detected by this method.…”
Section: Introductionmentioning
confidence: 99%